2014
DOI: 10.4236/as.2014.512117
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Methyl Jasmonate on Antioxidant Activity and Some Biochemical Aspects of Maize Plant Grown under Water Stress Condition

Abstract: A pot-culture study was undertaken to investigate the possible role of Methyl jasmonate (MeJA)treatment on the earlier vegetative growth stage and different chemical constituents of maize cultivar (Giza-2) plants subjected to water stress. The grains were divided into two groups: first group was pre-soaked in water, and the second one was pre-soaked in 50 μM MeJA for 8 h. The plants were subjected to different levels of water field capacity (WFC) 65%, 55% and 45%. The results showed that pre-soaking maize grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 50 publications
11
37
0
1
Order By: Relevance
“…In addition, irradiated seed with gamma rays and then sown at different salinity levels increased total amino acid. Abdelgawad et al (2014) showed that MeJA increased free amino acid content of maize plant compared to the corresponding untreated plant. (Karimi et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, irradiated seed with gamma rays and then sown at different salinity levels increased total amino acid. Abdelgawad et al (2014) showed that MeJA increased free amino acid content of maize plant compared to the corresponding untreated plant. (Karimi et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Ref. [52] demonstrate that MeJA treatment caused significant increases in total soluble sugar, polysaccharides and total carbohydrate in maize plants, as compared with the corresponding untreated plants.…”
Section: Soluble Carbohydratesmentioning
confidence: 85%
“…Ref. [52] found that MeJA increased total protein of maize plants compared to the corresponding untreated plant.…”
Section: Soluble Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…‫ﻣﺘﯿﻞ‬ ‫ﺟﺎﺳﻤﻮﻧﺎت‬ ‫ﺑﻪ‬ ‫ﻋﻨﻮان‬ ‫ﻫﻮرﻣﻮن‬ ‫اﻓﺰاﯾﺶ‬ ‫دﻫﻨﺪ‬ ‫ة‬ ‫آﻧﺘـﯽ‬ ‫اﮐﺴـ‬ ‫ﯿﺪان‬ ‫ﻫـﺎي‬ ‫ـﯽ‬ ‫ﻏﯿﺮآﻧﺰﯾﻤـ‬ ً ‫ـﺎ‬ ‫ﻏﺎﻟﺒـ‬ ‫ـﺐ‬ ‫ﺗﺮﻏﯿـ‬ ‫ـﻨﺘﺰ‬ ‫ﺳـ‬ ‫و‬ ‫ـﺎي‬ ‫ارﺗﻘـ‬ ‫ﻣﻘــﺎدﯾﺮ‬ ‫ـﺎ‬ ‫آﻧﻬـ‬ ‫از‬ ‫ـﻪ‬ ‫ﺟﻤﻠـ‬ ‫ـﺎروﺗﻦ‬ ‫ﺑﺘﺎﮐـ‬ ‫را‬ ‫ـﺎن‬ ‫ﻧﺸـ‬ ‫ـﯽ‬ ‫ﻣـ‬ ‫ـﺪ‬ ‫دﻫـ‬ . (Abdelgawad et al, 2014) ‫ﺗﺤﺖ‬ ‫آﻧﺘﻮﺳﯿﺎﻧﯿﻦ‬ ‫اﻓﺰاﯾﺶ‬ ‫ﺗﻨﺶ‬ ، ‫ﻫﻤﺎن‬ ‫در‬ ‫ﮐـﻪ‬ ‫ﻃﻮر‬ ‫ﺑـﺎرة‬ ‫ﮔﯿـﺎه‬ ‫ﺑﮕﻮﻧﯿـﺎ‬ ‫ﮐﺮده‬ ‫ﭘﯿﺸﻨﻬﺎد‬ ‫اﻧﺪ‬ (Ahmadi et al, 2004) . (Hernandez et al, 2004) .…”
unclassified